DESAIN DAN MANUFAKTUR BOX VACUUM FORMING DENGAN FINITE ELEMENT ANALYSIS - Nurdiana, Yuda; Wicaksono, Dhimas; Setiawan, Ferry (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
One of the manufacturing techniques often used in industry to produce various forms of plastic components. The research stage begins with designing a box using Solidworks software, Analysis carried out on the vacuum forming box structure using finite element analysis. The results obtained are in the form of maximum stress that occurs, displacement and safety factor. The vacuum forming box structure is also subjected to a load of 51.878 N or equivalent to 5.2901 kg. The location of the force given to the vacuum forming box structure with a vertical force direction downwards, the displacement that occurs in the vacuum forming box structure with a force of 51.878 N. The largest displacement occurs at the top center of the vacuum forming box surface with a displacement of 0.75 mm. This happens because in that section the area is free or does not have a support in the middle. the safety factor value that occurs in the vacuum forming box structure with a force of 51.878 N. The safety factor value used in this analysis is 1.5. The safety factor value obtained in the vacuum box structure is 1.8. The safety factor value requirement used, then based on the data obtained, the vacuum box structure using plywood material is safe in receiving a load of 51,878 N, because the FOS value obtained is greater than the FOS standard used. In testing the tool using PET plastic with a temperature of 100 ℃ and a time of 30 seconds, the testing process begins with the preparation of the appropriate PET plastic and is placed on the part or mold of the tool to be tested. The temperature of the tool is heated to 100 ℃.